Morbidities and mortalities in very low birth weight newborn a cohort study at tertiary care center of Central India - Mehar, Virendra; Muley, Swati; Agrawal, Saksham; Malhotra, Anuj (Indian Journal of Child Health, 2020)
Background: The survival in neonates is associated with their birth weights, gestation, and severity of illness. Despite all the efforts, the early neonatal mortality represents quite a high percentage. Objectives: The objectives of the study were to study the various short-term outcomes in with very low birth weight (VLBW) neonates. Materials and Methods: An observational hospital-based prospective cohort study was performed on live VLBW neonates admitted over a period of 1 year at the NICU of a tertiary hospital of Central India. Neonates with birth weight outside the study range or with major congenital anomalies and those with clinically identified chromosomal syndromes were excluded from the study. The hospital records of all neonates enrolled in the study were followed daily until the time of discharge for any morbidity. Results: A total of 116 neonates were recruited according to inclusion and exclusion criteria. There were 63 (54.3%) male and 53 (45.7%) female neonates considered in the study. The mean birth weight of VLBW neonates was 1282±136 g. Birth asphyxia was observed in 21% of the patients. Neonatal hyperbilirubinemia was the most common (36%) morbidity in these neonates. Conclusion: Almost half of the newborns had sepsis. Due to many factors such as optimization of neonatal care, better knowledge of the pathophysiology of the premature infant, the advent of exogenous surfactant therapy, and neonatal intensive care unit to handle sick infants, the survival rate in VLBW babies was higher in our study.